The Relationship Between Multimorbidity and Self-Reported Health Among Community-Dwelling Older Adults and the Factors that Shape This Relationship: A Mixed Methods Study Protocol Using CLSA Baseline Data. (28th September 2021) - Whitmore, Carly; Markle-Reid, Maureen; Fisher, Kathryn; Ploeg, Jenny; McAiney, Carrie; Griffith, Lauren; Phillips, Susan; Wister, Andrew
Self-reported health is a common measure predictive of morbidity and mortality among adults. Many factors are known to be associated with self-reported health including the number of chronic conditions (i.e., multimorbidity). While the association between self-reported health and morbidity and mortality has been well-established, the factors that shape the relationship with self-reported health (e.g., modify and mediate) are poorly understood. Further, it is unknown why some older adults, despite having high numbers of chronic conditions, continue to rate their health positively. This is known as the well-being paradox. This mixed methods research study was designed to address these knowledge gaps. The objectives of the proposed research are to (1) determine what factors shape the relationship between multimorbidity and self-reported health and how they do so; (2) describe the ways that older adults define and perceive their individual health; and (3) explain the well-being paradox. Informed by a multimorbidity resilience framework, the quantitative component of research will analyze Canadian Longitudinal Study on Aging data while the qualitative component will collect and analyze interview data from 12 to 20 community-dwelling older adults using a case study design. Findings from this study have the potential to inform and advance future health intervention programs or services aimed at improving health-related quality of life for community-dwelling older adults.